2003
DOI: 10.1093/humrep/deg420
|View full text |Cite
|
Sign up to set email alerts
|

Changes in extracellular matrix proteins in the cardinal ligaments of post-menopausal women with or without prolapse: a computerized immunohistomorphometric analysis

Abstract: In contrast to collagen I, our findings clearly indicate that collagen III expression is directly related to the presence of prolapse rather than age or menopausal status and is suppressed with the use of HRT. The pattern of change may fit a picture of healing phase of traumatized tissue as evidenced by the raised tenascin expression. The trauma itself may have been initiated by events such as childbirth, and that the lack of estrogen following the menopause results in decompensation. In spite of ameliorating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
94
1
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(108 citation statements)
references
References 26 publications
8
94
1
5
Order By: Relevance
“…Collagen is also the main organizational structural component connecting the pelvic organs (6). A number of studies have reported that collagen is involved in the pathogenesis of POP, and these studies have mainly focused on the collagen content, morphology and metabolism (7,8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen is also the main organizational structural component connecting the pelvic organs (6). A number of studies have reported that collagen is involved in the pathogenesis of POP, and these studies have mainly focused on the collagen content, morphology and metabolism (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Collagen is also a structural protein in the extracellular matrix (ECM) and is responsible for the integrity of the pelvic floor structure (6). Recent studies have demonstrated that the content, components and ultrastructure of collagen are modified in the pelvic floor structure of POP patients (7).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the cardinal ligaments reveals that 70-80% consists of collagen. 19 Collagen is thought to be one of the main determinants of biomechanical strength. There are approximately 28 types of collagen found in the human body, but the main subtypes in the pelvic floor are types I and III.…”
Section: Collagen Compositionmentioning
confidence: 99%
“…[20][21][22] Several studies have compared the amount of total and individual subtypes of collagen in the supporting ligaments and vaginal tissue of women with POP to a control group (see Table 1). 19,[23][24][25][26][27][28][29][30][31][32][33][34][35][36] Figure 1 Current anatomical considerations for prolapse. Level 1: The upper 1/3 of the vagina is suspended to the pelvic wall by the uterosacral and cardinal ligaments, condensations of endopelvic fascia.…”
Section: Collagen Compositionmentioning
confidence: 99%
“…Ewies et al (2003) and Karam et al (2007) demonstrated ) knockout mice with evidence of disrupted elastin fibers (Drewes et al, 2007). Lysyl oxidase-like1 (LOXL1) is a protein involved in the elastin fiber synthesis and assembly and LOXL1 knockout mice exhibit significant elastin fiber defects and POP in the postpartum period (Lee et al, 2008).…”
Section: Commentmentioning
confidence: 99%